Attitudes and behaviour of landholders towards the conservation of Overberg Coastal Renosterveld, a threatened vegetation type in the Cape Floral Kingdom - Winter, Susan Jean (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScConsEcol) -- Stellenbosch University, 2003.